Functionalization of Closed Schools of Province of Sindh, Pakistan: A Reform Strategy - Wasim, Qazi; M.H., Qazi; Khalid, Jamil Rawat; Imran, Qureshi (INTI International University, 2009)
Universalization of education has always been a challenge for the government of Pakistan, both at national and provincial levels. The Department of Education, Government of Sindh, has taken many initiatives to meet the basic requirements of the universalization of education in the province of Sindh. One such initiative was to gather information on the number of closed schools and to form a strategy to address the issue. The findings of the study reflect that there are 6034 schools which are dysfunctional. Out of a total of 6034 closed schools, each category of closed schools has to receive different strategic treatment. This paper presents a plan to be implemented in three phases for those schools which can be reclaimed. However, 1371 schools are ones which have been closed since 2001. For these schools it is suggested that this should be ignored